Understanding financial hardship in families of people living with dementia: Protocol for a scoping review to identify subjective self-report measures that evaluate financial hardship - Noelle E. Carlozzi; Christopher M. Graves; Jacqueline L. Freeman; Amanda N. Leggett; Jennifer A. Miner; Jin-Shei Lai; Madison Fansher; Minal R. Patel (PLoS ONE, 2025)
Background Financial hardship (including financial stress, financial strain, asset depletion, and financial toxicity) is a highly relevant construct among the 6.9 million people living with Alzheimer’s disease and related dementias (ADRD) in the United States and their family networks. This scoping review will identify existing measures and approaches for capturing financial strain among these families. Methods and Analysis This scoping review will be reported in accordance with PRISMA-ScR guidelines. Searches will be conducted in Embase (Embase.com), Medline (Ovid), CINAHLComplete (EbscoHost), AgeLine (EbscoHost), APA PsycInfo (EbscoHost), Scopus, and Web of Science Core Collection databases to identify tools, measures, or approaches for measuring self-reported financial hardship among family members of people living with ADRD. Data elements from both the National Health and Aging Trends Study and the associated National Study of Caregiving will also be considered. Two independent raters will screen the search results and discrepancies with be resolved by a third rater. Extraction will include the use of artificial intelligence-based software and verification by an independent human rater; any changes that are made to the AI-generated extraction will be reviewed by a second independent rater. A frequency analysis will be conducted to analyze the data, and a summary of the psychometric properties of each of the identified measures will be presented. Ethics and Dissemination The findings from this review will be disseminated through peer-reviewed publications and conference presentations. Ultimately, this work will inform the development of a new patient-reported outcome measurement system designed to provide a comprehensive assessment of the different aspects of financial hardship for families of people living with ADRD. Scoping Review Registration In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P), the following protocol was registered via https://osf.io on March 14, 2025 (registration DOI: https://doi.org/10.17605/OSF.IO/J26KT).